Automated tyre sorting system using mitsubishi FX3U PLC controller / Arnon Lerdwongpaisan - Arnon, Lerdwongpaisan (2013)
This research presents a case study of development of automated tyre sortation system by using integration of Programmable Logic Controller with barcode system. The objective of this research is to identify the possible improvements for tyre sortation system, increase flexibility of tyre sortation system by changing from manual to fully-automated, reduce hiring cost and the number of workers and reduce tasks of workers. Tyre sortation process is performed manually which is not flexible and can cause the mistake of sortation. Therefore, the manual sorting operation should be eliminated and the automated system should be developed or designed. Mitsubishi FX3U was chosen to integrate with barcode system and ladder diagram was designed to control the sorting operation. Laboratory test was performed to test the operation of program. The test shows that the program can work successfully. If this project is applied in the real process, it can increase flexibility, reduce task and number of operator and can save hiring cost of around 71,280 USD / year.